Ekstraksi Protein dari Rhodophyta dan Chlorophyta Dari Perairan Pulau Pari Sebagai Alternatif Antioksidant - Elvi Kustiyah; Bungaran Saingin; Hernowo Widodo; Viriya Piti (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2019)
Indonesia has millions island and big part of Indonesia is sea that is rich in marine biological resources and has the potential to be developed and optimized. One of the abundant marine resources in Indonesia is algae. Algae are plant-like protists. Algae have several important compounds, including protein, carbohydrates, fats, minerals and other useful elements. Proteins contained in algae have the potential to be used as antioxidants. In this study, the levels of protein in red and green algae were tested by using the lowry method and testing the antioxidant activity of red and green algae extracts using the Diphenylpicrylhydrazyl (DPPH) method. Algae extraction was done by maceration, which is soaking the sample in low temperature with phosphate buffer saline (PBS) pH 7. From the extraction results it can be concluded that the red algae (Rhodophyta) has the highest protein content of 5.115 ± 0.126% and the lowest protein content in green algae (Chloropytha) as big as 1.686 ± 0.430%. And from the results of the antioxidant activity test showed that all positive algae showed antioxidant activity but the green algae (Chlorophyta) had the highest antioxidant activity of 71.5946 ± 0.01612% with IC50 value 1.6114.